Public-Private Partnership (PPP) Projects for Malaysian Tolled Highways – An Insight using a Political Economy Approach - Alfan, Ervina (Asian Journal of Accounting Perspectives, 2012)
Tolled highways in Malaysia are built under the public-private approach in which the government provides the opportunities for the involvement of the private sector in the construction of these infrastructures. Using a political economy approach, this paper seeks to identify the main concession holders of the Malaysian tolled highways and ascertain in what way the tolled highways influence the political and economic arenas. This paper finds that the tolled highways in Malaysia play a significant role in achieving the country’s economic objectives.